Is Resilience Knowledge Related to the Mental Health of First-Year Medical Students? - Romadhona, Nurul; Fitriyana, Susan; Prasetia, Ayu; Ibnusantosa, Raden Ganang; Nurhayati, Eka; Respati, Titik (Global Medical & Health Communication (GMHC), 2023)
The many demands faced by first-year medical students can impact mental health. For students to function well, resilience is needed. This study aimed to determine the relationship between resilience knowledge and the mental health of first-year medical students. This quantitative study was conducted at the Faculty of Medicine, Universitas Islam Bandung, in October 2022. Respondents were 92 students in the first 2022/2023 academic year—data collection method was by distributing two Google Forms links. The first contains a pre-test regarding resilience knowledge, while the second includes the self-reporting questionnaire-29 (SRQ-29). Univariate analysis used distribution assumptions, frequency distribution (median, mean, standard deviation), and proportion distribution (percentage, 95% CI). Bivariate analysis used the ttest, Wilcoxon test, and chi-square test. Most respondents were female, 59% (95% CI=52.62, 72.37). The majority of respondents were 18 years old. The highest order of mental health screening was post-traumatic stress disordersymptoms at 59% (95% CI=48.27, 68.39), mental-emotional disorder (anxiety and depression) symptoms at 37% (95% CI=27.62, 47.37), and psychotic symptoms at 27% (95% CI 18.98, 37.28). No respondents experienced symptoms of narcotic or psychotropic drugs. Respondents who indicated mental health disorders were more significant than those who did not, namely 60% (95% CI=49.35, 69.39). There was no relationship between resilience knowledge and mental health (p=0.75). Respondent's understanding of resilience was good, but more indicated mental health disorders.